Beneficial Effects of Moderate Hepatic Activin A Expression on Metabolic Pathways, Inflammation, and Atherosclerosis. Issue 2 (1st December 2022) - Liu, Huan; Hallauer Hastings, Margaret; Kitchen, Robert; Xiao, Chunyang; Baldovino Guerra, Justin Ralph; Kuznetsov, Alexandra; Rosenzweig, Anthony
Abstract : Background: Atherosclerosis is an inflammatory vascular disease marked by hyperlipidemia and hematopoietic stem cell expansion. Activin A, a member of the Activin/GDF/TGFβ/BMP (growth/differentiation factor/transforming growth factor beta/bone morphogenetic protein) family is broadly expressed and increases in human atherosclerosis, but its functional effects in vivo in this context remain unclear. Methods: We studied LDLR − /− mice on a Western diet for 12 weeks and used adeno-associated viral vectors with a liver-specific TBG (thyroxine-binding globulin) promoter to express Activin A or GFP (control). Atherosclerotic lesions were analyzed by oil red staining. Blood lipid profiling was performed by high-performance liquid chromatography, and immune cells were evaluated by flow cytometry. Liver RNA-sequencing was performed to explore the underlying mechanisms. Results: Activin A expression decreased in both livers and aortae from LDLR − /− mice fed a Western diet compared with standard laboratory diet. Adenoassociated virus-TBG-Activin A increased Activin A hepatic expression ≈10-fold at 12 weeks; P <0.001) and circulating Activin A levels ≈2000 pg/ml versus ≈50 pg/ml; P <0.001, compared with controls). Hepatic Activin A expression decreased plasma total and LDL (low-density lipoprotein) cholesterol ≈60% and ≈40%, respectively), reduced inflammatory cells in aortae and proliferating hematopoietic stem cells in bone marrow, and reduced atherosclerotic lesion and necrotic core area in aortae. Activin A also attenuated liver steatosis and expression of the lipogenesis genes, Srebp1 and Srebp2. RNA sequencing revealed Activin A not only blocked expression of genes involved in hepatic de novo lipogenesis but also fatty acid uptake and liver inflammation. In addition, Activin A expressed in the liver also reduced white fat tissue accumulation, decreased adipocyte size, and improved glucose tolerance. Conclusions: Our studies reveal hepatic Activin A expression reduces inflammation, hematopoietic stem cell expansion, liver steatosis, circulating cholesterol, and fat accumulation, which likely all contribute to the observed protection against atherosclerosis. The reduced Activin A observed in LDLR −/− mice on a Western diet seems maladaptive and deleterious for atherogenesis.